Das Mündungsgebiet der Ahr im Spät-Würm und Holozän - Heine, Klaus (ERDKUNDE, 1982)
Proceeding from the recent morphodynamics in the area of the Ahr river mouth and the geomorphological-sedimentological investigation of the older lower terrace and the younger lower terrace of the Rhine and Ahr rivers it can be established that the transition from periglacial to Holocene processes of river dynamics and the change in the rivers’ outlines already occurred in the early Boiling period. Lesser periglacial conditions returned briefly during the Younger Dry as period. The most recent development of the mouth of the Ahr during the Holocene shows in model fashion the changes from a straight-flowing to a braided river.